Evaluating the Performance and Efficiency of MPPT Algorithm For PV Systems - Abdulwahhab Abdulrazzaq, Ali; Hussein Ali, Adnan (International Journal of Engineering and Technology, 2018)
Solar photovoltaic (PV) systems have an advantage of conversion sun's energy to electrical energy without regulation and lower efficiency due to I-V nonlinear characteristics that exhibits in the PV cells. Essentially, There is a need to maximize power extraction from these cells with a maximum power point tracking (MPPT) techniques. The performance of MPPT Algorithm involves a presentation of the PV system model with a most suitable method, Perturbation and Observation (P&O). The P&O implementation is done by MATLAB simulating, which covers a PV cell connected to a controlled buck converter by MPPT algorithms. The achievement of the P&O algorithm with a higher efficiency as well as be able to fast MPP tracking at the Constant irradiation condition as well as with variable irradiation.Â Â